2002
DOI: 10.1038/ng985
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in IRF6 cause Van der Woude and popliteal pterygium syndromes

Abstract: Interferon regulatory factor 6 (IRF6) belongs to a family of nine transcription factors that share a highly conserved helix-turn-helix DNA-binding domain and a less conserved protein-binding domain. Most IRFs regulate the expression of interferon-alpha and -beta after viral infection, but the function of IRF6 is unknown. The gene encoding IRF6 is located in the critical region for the Van der Woude syndrome (VWS; OMIM 119300) locus at chromosome 1q32-q41 (refs 2,3). The disorder is an autosomal dominant form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
840
3
62

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 813 publications
(932 citation statements)
references
References 25 publications
27
840
3
62
Order By: Relevance
“…10,11 In addition, IRF6 (interferon regulatory factor 6) and RIPK4 have been implicated in PPS. 8,9,12 We found that similar to IRF6 mutants, 10,11,13 RIPK4 − / − mice 1 have a defective skin barrier function and cleft palate, and RIPK4 − / − keratinocytes fail to differentiate in vitro. In Xenopus, we show that IRF6 controls RIPK4 expression and that RIPK4 can rescue developmental defects imposed by IRF6 dysfunction, thereby identifying a novel genetic interaction between IRF6 and RIPK4.…”
mentioning
confidence: 80%
“…10,11 In addition, IRF6 (interferon regulatory factor 6) and RIPK4 have been implicated in PPS. 8,9,12 We found that similar to IRF6 mutants, 10,11,13 RIPK4 − / − mice 1 have a defective skin barrier function and cleft palate, and RIPK4 − / − keratinocytes fail to differentiate in vitro. In Xenopus, we show that IRF6 controls RIPK4 expression and that RIPK4 can rescue developmental defects imposed by IRF6 dysfunction, thereby identifying a novel genetic interaction between IRF6 and RIPK4.…”
mentioning
confidence: 80%
“…In the other report, a mutation, Glu92X, in interferon regulatory factor 6 (IRF6) was identified in a MZ twin having Van der Woude syndrome characterized by the cleft lip and palate with lip pits, whose healthy co-twin did not have this disease. 21 This mutation was not found in healthy co-twins and their parents. They reported this finding as one of the evidences to prove the causative role of IRF6 in Van der Woude syndrome.…”
Section: Geneticmentioning
confidence: 91%
“…Post-zygotic de novo mutations, as well as epigenetic differences are mechanisms proven to underlie MZ twin discordance [Kondo et al, 2002;Weksberg et al, 2002]. The latter mechanism has been documented in twins with Beckwith Wiedemann syndrome (BWS).…”
Section: De Novo Mutations Responsible For Cdhmentioning
confidence: 99%
“…The discovery of mutations in the interferon regulatory factor 6 gene (IRF6) as the cause of lip pit or van der Woude syndrome could be a model for identifying multifactorial genetic changes contributing to CDH. Specifically, mutations in both the IRF6 protein binding domain and the DNA binding domain produce van der Woude syndrome; recent studies demonstrate that a common variant in IRF6 increases the risk for isolated cleft lip and palate [Kondo et al, 2002;Kayano et al, 2003;Zucchero et al, 2004;Scapoli et al, 2005]. Thus, possible mutations or clusters of polymorphisms in FOG2, WT1 and, other as yet unidentified major development genes or their downstream targets, could contribute to multifactorial causation of CDH.…”
Section: Further Evidence That Cdh Has Genetic Determinantsmentioning
confidence: 99%